Teaching Exploration and Practice of Advanced Chemical Separation Course for Master’s Degree Students in Chemical Engineering - Yang Qian; Yao Binghua; Niu Jinfen; He Yangqing; Yu Xiaojiao (SHS Web of Conferences)
Advanced Chemical Separation is a core course for chemical engineering master’s students, characterized by its broad scope, interdisciplinary nature, and strong practical orientation. To address challenges such as numerous knowledge points, integration difficulties, rapid updates in frontier knowledge, and insufficient engineering problem integration, the teaching team explored innovative approaches based on the “Three Parallel Education” concept. This includes course content design, teaching mode innovation, and the integration of ideological and political education, providing a reference for the reform of engineering graduate courses in the new era.